Cytokine profile in lung transplant recipients with Aspergillus spp colonization. Issue 3 (21st March 2019) - Herrera, Sabina; Gohir, Wajiha; Foroutan, Farid; Aguilar, Claire; Juvet, Stephen; Martinu, Tereza; Kumar, Deepali; Humar, Atul; Rotstein, Coleman; Keshavjee, Shaf; Singer, Lianne G.; Husain, Shahid
Abstract: We studied cytokine profiles in BAL of LTRs with Aspergillus spp colonization who did not progress to IPA in the absence of antifungal prophylaxis. This was a retrospective, single center case‐control study. BAL samples were analyzed for cytokines. Patients with Aspergillus spp in BAL who did not receive prophylaxis and did not develop IPA were compared to LTRs with Aspergillus spp that received prophylaxis, LTRs with IPA and controls. Twenty‐one patients with Aspergillus colonization who did not develop IPA, seven patients with suspected IPA who received prophylaxis, 4 IPA and 19 controls were included. IPA group had significantly higher levels (median [IQR]) of MIP‐1 beta compared to the Suspected IPA group (5 vs 5 P : 0.03). The Suspected IPA group had significantly higher levels of IL‐12 (11.38 vs 1 P : 0.0001), IL‐1 RA (86.11 vs 23.98 P : 0.0118), IP‐10 (22.47 vs 0.86 P : 0.0151), HGF (40.92 vs 16.82 P : 0.0055), and MIG (169.62 vs 5 P : 0.0005) than Colonization group. We have identified a unique cytokine signature in patients with Aspergillus colonization that do not develop IPA. Our study forms basis for a larger study to use these cytokines profile to identify patients at a lower risk of developing IPA.